2021
DOI: 10.3389/fendo.2021.656106
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroids Toxicity to Male Reproductive System and Offspring as a Function of Oxidative Stress Induction: Rodent Studies

Abstract: Pyrethroids may be related to male reproductive system damage. However, the results of many previous studies are contradictory and uncertain. Therefore, a systematic review and a meta-analysis were performed to assess the relationship between pyrethroid exposure and male reproductive system damage. A total of 72 articles were identified, among which 57 were selected for meta-analysis, and 15 were selected for qualitative analysis. Pyrethroid exposure affected sperm count (SMD= -2.0424; 95% CI, -2.4699 to -1.61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 84 publications
3
23
0
Order By: Relevance
“…These findings were in line with most of the studies which suggested that LCH exposure causes depletion of proteins by causing the destruction or necrosis of cellular function and consequent impairment in protein synthetic machinery [8] , [13] , [18] , [33] . As most of the pyrethroids inflict intense oxidative stress even in the adult tissues and organs [3] , [36] , it is proposed that LCH exposure in present study must have led to an intense increase in the reactive oxygen radicals in the developing embryos as the metabolic rate of the differentiating tissues and organs is naturally much higher than the adult tissues and are more prone to oxidative damage. Additionally, the embryonic tissues are less differentiated and are thus metabolically insufficient to metabolize the insecticide and to get rid of its metabolites and also to combat with the reactive oxygen species generated on insecticide exposure [21] , [24] .…”
Section: Discussionmentioning
confidence: 95%
“…These findings were in line with most of the studies which suggested that LCH exposure causes depletion of proteins by causing the destruction or necrosis of cellular function and consequent impairment in protein synthetic machinery [8] , [13] , [18] , [33] . As most of the pyrethroids inflict intense oxidative stress even in the adult tissues and organs [3] , [36] , it is proposed that LCH exposure in present study must have led to an intense increase in the reactive oxygen radicals in the developing embryos as the metabolic rate of the differentiating tissues and organs is naturally much higher than the adult tissues and are more prone to oxidative damage. Additionally, the embryonic tissues are less differentiated and are thus metabolically insufficient to metabolize the insecticide and to get rid of its metabolites and also to combat with the reactive oxygen species generated on insecticide exposure [21] , [24] .…”
Section: Discussionmentioning
confidence: 95%
“…However, there are also some limitations to bioinformatics analysis. First, without experimental verification, the results need to be verified by experiments [ 40 ]. In addition, high heterogeneity often leads to large bioinformatics analysis errors, so unifying the methods is essential to reducing errors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Permethrin is a broadly used, long-lasting pyrethroid insecticide coated on fabrics and mosquito nets, particularly in malaria-endemic countries enforcing control programs to curtail disease transmission. Permethrin also has some toxicity concerns, including a reduction in male fertility parameters and reduced testosterone demonstrated in rodent studies ( 65 ) as well as hepatotoxicity ( 66 ). The widespread use of pyrethroid insecticides has gained exponential traction over the past few years as mosquitos have developed pyrethroid resistance.…”
Section: Mosquito Bite Prevention and Recent Developmentsmentioning
confidence: 99%